The Devil in William Blake’s The Marriage of Heaven and Hell: confluences with the reception of Paradise Lost’s Satan in the eighteenth century - Wanderlinde, William Weber (2024)
This article aims to analyze how the Devil is depicted in The Marriage of Heaven and Hell (1790), written by English writer William Blake, mainly by comparing it with readings of the character Satan, from John Milton’s Paradise Lost (1667). Firstly, an analysis of several readings of John Milton’s Satan is carried out. These readings encompass texts and engravings from the eighteenth century, and are related to the evaluation of Milton’s epic poem through an Aristotelian rationality. The two last decades of the eighteenth century are treated more attentively since a change of paradigm in relation to the readings of Satan seems to occur in them.  Finally, a reading of The Marriage of Heaven and Hell which looks for similarities and differences with the previously analyzed readings is done. The conclusion is that this book presents a vision of the Devil which is similar to some readings of the end of the eighteenth century but differs from those in the crucial role of the Devil in the text.